2021
DOI: 10.3390/ijms222111455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Toxic Metals Arsenite and Cadmium on α-Synuclein Aggregation In Vitro and in Cells

Abstract: Exposure to heavy metals, including arsenic and cadmium, is associated with neurodegenerative disorders such as Parkinson’s disease. However, the mechanistic details of how these metals contribute to pathogenesis are not well understood. To search for underlying mechanisms involving α-synuclein, the protein that forms amyloids in Parkinson’s disease, we here assessed the effects of arsenic and cadmium on α-synuclein amyloid formation in vitro and in Saccharomyces cerevisiae (budding yeast) cells. Atomic force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…In Figure 3a , we show AFM images for the three aS amyloids, formed without and with the presence of 0.5 molar ratio of Cu(II). All amyloids showed fibril heights of around 6–8 nm, regardless of Cu(II), which is according to the literature for aS amyloids (Lorentzon et al, 2021 ). However, the twisting pattern (periodicity) along the fibers, denoted as a fiber pitch, varied between the three aS variants and if Cu had been added or not (Figures 3b and S5 ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In Figure 3a , we show AFM images for the three aS amyloids, formed without and with the presence of 0.5 molar ratio of Cu(II). All amyloids showed fibril heights of around 6–8 nm, regardless of Cu(II), which is according to the literature for aS amyloids (Lorentzon et al, 2021 ). However, the twisting pattern (periodicity) along the fibers, denoted as a fiber pitch, varied between the three aS variants and if Cu had been added or not (Figures 3b and S5 ).…”
Section: Resultssupporting
confidence: 87%
“…Today, many high-resolution structures of amyloids have been described and it clear that there are many amyloid folds possible for the same protein sequence (Sawaya et al, 2021). Metal ions, such as Cu (shown here, but also As(III) and Cd(II) (Lorentzon et al, 2021)), may be responsible for some of the structural diversity of aS amyloids, along with effects of other environmental factors. The connection between amyloid polymorph and pathological consequences may be related to differences in cell-cell spreading and toxicity among amyloid polymorphs.…”
Section: Discussionmentioning
confidence: 87%
“…Consistently, previous in vitro studies indicated that As(III) binding can influence the structure of aggregated model proteins. As(III) interacted with and modulated the amyloid fiber structure of the Parkinson’s disease–associated protein α-synuclein ( 18 ) and monomethylated arsenite (monomethylarsenous acid) induced the formation of amyloid-like fibrils of bovine pancreatic ribonuclease A ( 52 ). Constrained dynamics of polypeptides within the aggregate might limit the ability of chaperones to penetrate the surface and to access their binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…These responses mitigate the proteotoxic effects of As(III) by restricting intracellular arsenic levels, protecting the proteome from harmful arsenic interactions, and preventing the detrimental accumulation of misfolded and aggregated proteins ( 11 , 13 , 14 , 15 , 17 ). The impact on protein homeostasis and PQC contributes to the toxicity of arsenic and may underlie its suspected role in the etiology of protein misfolding disorders ( 8 , 10 , 11 , 12 , 13 , 18 ). Nevertheless, much remains to be understood about the mechanistic details of how As(III)-induced protein aggregates are formed in vivo and how cells regulate PQC systems to protect against toxic aggregates.…”
mentioning
confidence: 99%
“…Such structural variations observed within the amyloid aggregates formed from the same precursor protein can potentially account for the observed disease phenotypes. A growing body of research has revealed that an intrinsically disordered presynaptic neuronal protein, α-synuclein (α-syn), self-assembles into various structurally distinct fibrillar assemblies in vitro and in vivo and exhibits prion-like strain phenomena. The remarkable conformational plasticity of α-syn allows it to adopt multiple conformational states that can potentially propagate via a prion-like mechanism. α-Syn forms higher molecular weight assemblies progressively in the nerve and glial cells to form intracellular pathological lesions termed Lewy bodies and Lewy neurites, which are the pathological hallmark of a diverse group of debilitating neurodegenerative disorders termed synucleinopathies, such as Parkinson’s disease, dementia with Lewy bodies, and multiple system atrophy. , The polymorphic landscape of amyloid assembly is highly sensitive to a multitude of environmental factors, such as temperature, incubation times, buffer compositions, pH, ionic strength, post-translational modifications, and the presence of cofactors, as well as variation in the primary amino acid sequence. Such in vitro modifications in the fibril assembly conditions can alter the molecular interactions between the polypeptide chains and influence the conformation, as well as pathology, of distinct fibrillar assemblies, which can either propagate as an amyloid strain or simply form polymorphs. …”
mentioning
confidence: 99%